Relationship between Chemotherapy and Atrial Fibrillation: Clinical Case - A. A. Avagimyan; L. H. Mkrtchyan; A. A. Gevorkyan; N. B. Kononchuk; L. V. Kakturskiy; Z. T. Djndoyan (Рациональная фармакотерапия в кардиологии)
The aim of this article is to represent the characterization of the clinical case of chemotherapy-related atrial fibrillation (AF) development in the young woman, elaborated as a result of multiple neoadjuvant and adjuvant modes of the intake of chemotherapy (both anthracycline based and non-anthracycline ones). In this case, the noted disturbances of heart rhythm should be recognized as a manifestation of cardiotoxicity. The latter implies the degree of detrimental effect of chemotherapeutical medication on the morphophynctional parameters of the cardiovascular system. Anthracycline drugs, being highly effective chemotherapytical agents, provide well-known toxic effects on the heart and vessels. Anthracycline mediated cardiotoxicity is a well- known veracity that dates back to the 60s of the last century, but up to now this medication sustains irreplaceable components of big volume of chemotherapy modes. Moreover, it should be noted that relatively newer drugs also posses certain cardiotoxicogenic potential.